EURECA: End‐user requirements engineering with collaborative animation. (11th April 2017) - Kim, Neunghoe; Park, Soojin; Jeong, Dongwon; Hwang, Mansoo; Park, Sooyong; In, Hoh Peter
Summary: In recent years, software development environments have changed from being driven by professional developers to being driven by technical end users. One of the key issues in end‐user‐driven software development environments is how to guarantee the quality of the software artifacts. Measuring the quality of developed software requires the correct specification of a quality range the software is expected to meet. However, technical end users are non‐professionals in engineering techniques for software requirements, and training a developer to be an expert in requirements engineering in a short period of time is difficult. This paper proposes a new software development life cycle based on reutilizing previously evaluated software requirements assets from completed projects. End‐User Requirements Engineering with Collaborative Animation, a tool that was developed to support the proposed software development life cycle, is described and demonstrated by application to three projects. The results from real cases are used as the basis for a discussion on the efficiency enhancement of requirements work, an increased rate of reusing legacy software requirements assets, and an improvement in the technical end user's individual competency level using the End‐User Requirements Engineering with Collaborative Animation. Copyright © 2017 John Wiley & Sons, Ltd.